Boolean Algebra

Logic Level 2

¬ ( ¬ ( p q ) ¬ ( q p ) ) \neg \big(\neg (p \implies q) \implies \neg (q \implies p)\big)

Which of the given options is equivalent to the above Boolean expression?

¬ p q \neg p \wedge q ( p q ) ¬ ( ¬ p ¬ q ) (p\wedge q) \wedge \neg (\neg p \wedge \neg q) p q p \iff q ¬ ( p q ) \neg(p \implies q)

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Ashish Menon
Apr 21, 2016

( ( p q ) ( q p ) ) \backsim (\backsim (p \rightarrow q) \rightarrow \backsim (q \rightarrow p))
= \backsim ( \backsim (p \rightarrow q) \rightarrow (q ^ \backsim p))
= \backsim (p \rightarrow q) ^ \backsim (q ^ \backsim p)
= (p ^ \backsim q) ^ ( \backsim q v p)
= (p ^ \backsim q)
= ( p q ) \boxed{\backsim (p \rightarrow q)}

Why in step 2 you dont put the negation in the first implication?

Alessandro Rubio - 4 years, 6 months ago

Log in to reply

Cuz if i do, then it would become a but more complex and we would have to use the truth tabke to get the final result. Instead lets keep it as it is and bring it in the form ( P Q ) \backsim \left( P \rightarrow Q\right) so that we can again simply it into P \text{^} \backsim Q .

Ashish Menon - 4 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...